Assessing the impacts of labour skill improvement in Bolsa Família Program beneﬁciaries: a computable general equilibrium model analysis - Wolf, Rayan (2021)
Government transfers to Brazilian families through the Bolsa Família Program have a dual impact on beneĄciaries. In the beginning, it plays a fundamental role in raising the well-being of the poorest families, increasing consumption, and temporarily alleviating poverty. In the long term, however, it inhibits the durability of the effects by reducing the price of the labor factor, the main source of income for the poorest families. In this way, the objective of the present study was to evaluate the economic impacts of a policy of qualiĄcation of work through professional courses for beneĄciary families of Bolsa Família in Brazilian regions. To achieve this objective, the DAYANE model was built, a computable, static, multiregional, and multisectoral general equilibrium applied model. The model is based on the Global Trade Analysis Project (GTAP) and the General Equilibrium Analysis Project of the Brazilian economy (PAEG), presenting Brazil divided into Ąve macro-regions and families divided into ten income classes, in each Brazilian region. Unlike the PAEG, the DAYANE model is developed in GEMPACK language and disaggregates familiesŠ schooling into twelve different levels. In building the model, in addition to making the PAEG compatible with the GEMPACK, the preparation of the database required the disaggregation of schooling levels for each income class in the Brazilian regions; of the workforce employed in each sector, by income class in the Brazilian regions; and, of the workforce employed in each sector, by the level of education in the Brazilian regions. In the model, labor qualiĄcation shocks were simulated for beneĄciaries of the Bolsa Família Program, via vocational courses, from the complete basic and incomplete fundamental levels, and the income of families from the Bolsa Família Program is reduced in proportion to the increase in salary. The results of the study indicate that the qualiĄcation of labor, via professional courses, has positive impacts on the wages of families in Brazilian regions, especially in the poorest regions of Brazil. In addition, the study shows that even removing income transfers, via the Bolsa Família Program, in proportion to the increase in the familiesŠ salary, the positive results in the total family income are still maintained, and consumption increases. In this way, the study shows that labor qualiĄcation policies for families dependent on the Bolsa Família Program improve their economic situation, with income from transfers being replaced by income from work, which indicates that government transfers can cease in response to better gains in the labor market, and also ensure the economic improvement of families dependent on the Program. Keywords: Welfare. Bolsa Família Program. Skill improvement. Labour market.